2016
DOI: 10.1111/dom.12602
|View full text |Cite
|
Sign up to set email alerts
|

Once‐weekly glucagon‐like peptide‐1 receptor agonist dulaglutide significantly decreases glycated haemoglobin compared with once‐daily liraglutide in Japanese patients with type 2 diabetes: 52 weeks of treatment in a randomized phase III study

Abstract: AimsTo examine the efficacy and safety of once‐weekly dulaglutide 0.75 mg monotherapy compared with once‐daily liraglutide 0.9 mg in Japanese patients with type 2 diabetes (T2D) for 52 weeks.MethodsWe conducted a phase III, randomized, 52‐week (26‐week primary endpoint), active‐ and placebo‐controlled trial comparing 492 Japanese patients (dulaglutide, n = 281; liraglutide, n = 141; and placebo, n = 70). Participants and investigators were blinded to treatment assignment for dulaglutide and placebo but not for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
101
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(114 citation statements)
references
References 23 publications
11
101
0
2
Order By: Relevance
“…Hence, it requires no dose adjustment for use in patients with renal impairment. Furthermore, a phase III clinical study reported that once-weekly dulaglutide significantly reduced HbA1c levels in type 2 diabetes mellitus patients with normal renal function compared to once-daily liraglutide after 52 weeks (11). In our study, once-weekly dulaglutide significantly reduced HbA1c levels with no adverse effects in patients with advanced-stage diabetic nephropathy after changing from once-daily liraglutide.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Hence, it requires no dose adjustment for use in patients with renal impairment. Furthermore, a phase III clinical study reported that once-weekly dulaglutide significantly reduced HbA1c levels in type 2 diabetes mellitus patients with normal renal function compared to once-daily liraglutide after 52 weeks (11). In our study, once-weekly dulaglutide significantly reduced HbA1c levels with no adverse effects in patients with advanced-stage diabetic nephropathy after changing from once-daily liraglutide.…”
Section: Discussionsupporting
confidence: 54%
“…Dulaglutide, a long-acting GLP-1 receptor agonist, can be used by once-weekly administration in patients with diabetes mellitus and impaired renal function without any dose adjustment (8)(9)(10). Dulaglutide showed better glucose control compared to liraglutide, a once-daily GLP-1 receptor agonist, in patients with type 2 diabetes mellitus and normal renal function (11). Dulaglutide has also been reported to show nephroprotective effects in patients with type 2 diabetes mellitus with mild renal impairment (12).…”
Section: Introductionmentioning
confidence: 99%
“…gov (NCT01584232, NCT01558271, NCT01468181). Study design and methods for each study have been previously reported [7][8][9][10].…”
Section: Patientsmentioning
confidence: 99%
“…In phase 3 studies in Japanese patients with T2D, once weekly dulaglutide 0.75 mg has shown superiority to insulin glargine (in a randomized, 26-week, open-label study of dulaglutide in combination with sulfonylureas [SU] and/or biguanides [BG]) and non-inferiority to liraglutide 0.9 mg/day (in a randomized monotherapy study in which dulaglutide was compared to placebo [double-blind] and to liraglutide 0.9 mg/day [open-label]; the study had a 26-week primary endpoint and a 52-week treatment period) in HbA1c changes [7][8][9]. Also, in a nonrandomized, open-label, long-term (52-week) phase 3 safety study in Japanese patients with T2D, once weekly dulaglutide 0.75 mg was overall well-tolerated in combination with a single oral hypoglycemic agent (SU, BG, α-glucosidase inhibitors, thiazolidinediones, or glinides) [10].…”
mentioning
confidence: 99%
“…Dulaglutide is a once weekly GLP-1 receptor agonist approved in Japan at a dose of 0.75 mg. After 26 apy study" [8,12], which was a 52-week study that had the primary endpoint at 26 weeks, and 2) "the combination study" [9], which was a 26-week study. The monotherapy study randomized patients to dulaglutide, liraglutide 0.9 mg, or placebo; after 26 weeks of treatment, patients treated with placebo were switched to dulaglutide.…”
mentioning
confidence: 99%